2009
DOI: 10.1213/ane.0b013e3181adc506
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dexmedetomidine with Propofol for Magnetic Resonance Imaging Sleep Studies in Children

Abstract: Dexmedetomidine provided an acceptable level of anesthesia for MRI sleep studies in children with OSA, producing a high yield of interpretable studies of the patient's native airway. The need for artificial airway support during the MRI sleep study was significantly less with dexmedetomidine than with propofol. Dexmedetomidine may be the preferred drug for anesthesia during MRI sleep studies in children with a history of severe OSA and may offer benefits to children with sleep-disordered breathing requiring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
92
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(104 citation statements)
references
References 49 publications
9
92
0
3
Order By: Relevance
“…Dexmedetomidine, which does not commonly result in respiratory depression, may be the optimal option for patients with pre-existing severe airway obstruction. Mahmoud et al (10) found that, compared with the use of propofol, dexmedetomidine showed improved preservation of the upper airway muscle tone and minimal airway collapsibility. Furthermore, ketamine has been shown to preserve the hypopharyngeal size in adults (11); however, this compound tends to increase respiratory secretions and induce laryngospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, which does not commonly result in respiratory depression, may be the optimal option for patients with pre-existing severe airway obstruction. Mahmoud et al (10) found that, compared with the use of propofol, dexmedetomidine showed improved preservation of the upper airway muscle tone and minimal airway collapsibility. Furthermore, ketamine has been shown to preserve the hypopharyngeal size in adults (11); however, this compound tends to increase respiratory secretions and induce laryngospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is a limitation on use of propofol in remote anesthesia because it increases the risk of respiratory depression. Dexmedetomidine has been shown to have sedative properties without respiratory depression it seemed to us that dexmedetomidine had many characteristics of ideal sedative for remote anesthesia in pediatric radiotherapy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam eklenmesi çocuk hastalarda derlenme ve taburculuk sürelerini uzatmaktadır. [12,13] Sonuç olarak, MRG işlemi esnasında günü birlik anestezi verilen hastalarda son yıllarda kullanılmaya başla-nan propofolün özellikle hemodinamik değişiklikler, MRG işlemine hazır hale gelme süreleri, derlenme …”
Section: Discussionunclassified